Number of nodal metastases and the American Joint Committee on cancer staging of head and neck cutaneous squamous cell carcinoma: A multicenter study. (December 2020) - Ebrahimi, Ardalan; Gupta, Ruta; Luk, Peter; Low, Tsu-Hui (Hubert); McDowell, Lachlan; Magarey, Matthew J.R.; Smith, Paul N.; Perriman, Diana M.; Schulte, Klaus-Martin; Veness, Michael; Porceddu, Sandro V.; Clark, Jonathan R.
Highlights: This multicentre collaborative study of 1128 patients represents the largest reported cohort of patients with nodal metastases from head and neck cutaneous squamous cell carcinoma (HNcSCC) Nodal metastases are an independent predictor of survival in metastatic HNcSCC. Categorization as 1–2, 3–4 and ≥5 metastatic nodes optimizes risk stratification and prognostic discrimination. This simple categorical variables provides superior prognostic information to the AJCC TNM stage based on objective measures. Abstract: Objectives: We aimed to determine if the number of nodal metastases is an independent predictor of survival in HNcSCC, whether it provides additional prognostic information to the AJCC N and TNM stage and identify optimal cut-points for risk stratification. Materials and methods: Retrospective multi-institutional cohort study of patients with parotid and/or cervical nodal metastases from HNcSCC treated with curative intent by surgery ± adjuvant therapy. The impact of number of nodal metastases on disease-specific and overall survival was assessed using multivariate Cox regression. Optimal cut-points for prognostic discrimination modelled using the AIC, BIC, C-index and PVE. Results: The study cohort included 1128 patients, with 962 (85.3%) males, median age of 72.9 years (range: 18–100 years) and median follow-up 3.4 years. Adjuvant radiotherapy was administered to 946 (83.9%) patients. Based on objective measures of model performance, number of nodal metastases was classified as 1–2 (N = 816), 3–4 (N = 162) and ≥5 (N = 150) nodes. In multivariate analyses, the risk of disease-specific mortality progressively increased with 3–4 nodes (HR, 1.58; 95% CI: 1.03–2.42; p  = 0.036) and ≥5 nodes (HR, 2.91; 95% CI: 1.99–4.25; p  < 0.001) with similar results for all-cause mortality. This simple categorical variable provided superior prognostic information to the TNM stage. Conclusion: Increasing number of nodal metastases is an independent predictor of mortality in HNcSCC, with categorization as 1–2, 3–4 and ≥5 nodes optimizing risk stratification and providing superior prognostic information to TNM stage. These findings may aid in the development of future staging systems as well as identification of high-risk patients in clinical trials.